Pemberdayaan UMKM Produk Mahar Melalui Pelatihan Digitalisasi Pemasaran Pada Rona Creation Nganjuk - Chamid, Nur; Yuliani, Yuliani; Amalia, Fransisca; Putri, Oktaria Ardhika (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This study discusses how to use social media in the midst of the Covid-19 pandemic as a marketing medium for Rona Creation's UMKM